Pengaruh Intensitas Penggunaan Smartphone Terhadap Prestasi Belajar Siswa Kelas V pada Bidang Studi Fiqih: Studi Kasus di Madrasah Ibtidaiyah Al-Istiqomah Mojongapit Jombang - Adibah Adibah; Fathur Rofi'i; Muhammad Shofiyul Izza (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
The purpose of this study was to determine whether or not there is an Influence of Smartphone Usage Intensity on the Learning Achievement of Fifth Grade Students in the Field of Fiqh Studies at the Al-Istiqomah Mojongapit Jombang Elementary Madrasah. This type of research is quantitative research, namely scientific research that focuses on collecting numerical data and statistical analysis to answer research questions and test hypotheses. Data collection uses observation, questionnaires, documentation and interviews. While the data analysis uses statistical analysis using the Chi Square formula. Based on the results of the research conducted, it was concluded that there is no Influence of Smartphone Usage Intensity on the Learning Achievement of Fifth Grade Students in the Field of Fiqh Studies at the Al-Istiqomah Mojongapit Jobang Elementary Madrasah. This can be proven by the results of the Chi Square calculation (X²) which shows X is greater than (>) X¹ the critical value is 5.6 greater than 6.635. means the working hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted. Keywords: Smartphone; Learning Achievement; Field of Fiqh Studies